STINGRAY MIRACLE IN CLOTHING WEDDING - Sausan Husin Abdat (Canthing, 2014)
Designing clothing is aimed to design a wedding dress with a source of ideas stingrays. References lead fashion renaissance period clothing, the color used terinpirasi of color stingray realized in three colors: white, yellow, brown novelty innovation techniques in materials and the addition of tie dye as a manifestation of the tradition of Indonesia.The design of this fashion through several phases, namely: persiapann stage consists of making fashion design, collection size, clothing pattern making, material selection, design and price of materials, sewing, making innovation and tie dye, fitting, and settlement. Being a wedding dress for adult women consists of thre pieces. Taking renaissance silhouette and asymmetrical pieces on every detail of clothing.